PERTANGGUNGJAWABAN RUMAH SAKIT AKIBAT KELALAIAN TENAGA KESEHATAN DALAM PELAYANAN TERHADAP PASIEN NON COVID PADA MASA PANDEMI COVID-19 - Ni Putu Yogi Satya Ardiniswari; Satya Ardiniswari, Ni Putu Yogi; Irfan, Muhammad (Faculty of Law, University of Mataram, 2024)
This study aims to identify the factors causing negligence by healthcare workers in providing services to non-COVID patients during the COVID-19 pandemic and the accountability for such negligence in patient care during the pandemic at the Public Hospital of Mataram City. The research employs an empirical legal study with legislative, conceptual, and field data approaches, utilizing sources and types of data gathered through literature reviews and interviews with patient families and the Head of the Public Hospital of Mataram City. The results indicate: First, the factors leading to healthcare worker negligence include the failure to meet medical service obligations in accordance with professional standards, operational procedure standards, and patient needs. When a healthcare worker fails to fulfill these obligations, it can result in severe consequences for the patient. Second, the legal accountability of the Public Hospital of Mataram City for healthcare worker negligence during the COVID-19 pandemic relies on collaboration with the Indonesian Medical Association (IDI) and the police. Other forms of accountability are governed by civil law based on Article 1365 of the Civil Code, criminal law under Article 351 of the Criminal Code, and administrative law in the form of license revocation.